The evaluation of a simulated theatre scenario as a tool to promote inter-professional collaboration and engender a culture of increased awareness of patient safety in South African hospitals - Robertson, Caroline Helen (Department of Anaesthesia and Perioperative Medicine, 2023)
Background: Errors related to patient safety are a major contributor to adverse incidents and preventable deaths. Interventions aimed at changing team behaviour and implementing World Health Organisation Safe Surgical Checklists (WHO SSCL) have been associated with improved outcomes. We required a cost- and timeefficient vehicle to address low adoption rates of the WHO SSCL, barriers to interdisciplinary teamwork, and inadequate attention to patient safety. Method: We aimed to test the feasibility and efficacy of a simulation-based intervention to improve behaviour influencing patient safety in operating theatres. We performed a prospective cohort study using survey tools for attendee feedback immediately after the event and at 6 weeks. We report feasibility and efficacy data plus qualitative feedback from the education team describing the advantages of this instructional design. The intervention was a 2-stage simulation. First, learners watched a 5-minute film, set in the operating theatre, depicting an error-filled WHO SSCL timeout. Second, learners entered a simulated operating theatre environment with multiple errors and risks to patient safety. Learners identified errors and prioritised them in order of importance. Their observations were discussed in a small group debrief session facilitated by novice debriefers before a whole group plenary discussion. Results: One hundred and three health workers attended the education event and 77 (75%) responded to the Immediate Questionnaire. Surgeons (27), Anaesthetists (18) and Scrub Nurses (12) made up the majority of respondents. Sixty-seven (87%) participants agreed or strongly agreed that they “now have an increased awareness of patient safety”, while 75 (97%) agreed or strongly agreed that they “feel more committed to ensuring a team approach to patient safety”. Thirty (29%) attendees responded to the Delayed Questionnaire distributed via email 6 weeks after the event. Twenty-eight (93%) agreed or strongly agreed that they felt more committed to ensuring a team approach to patient safety. Conclusion: The total cost of the event was low. Faculty reported that the instructional design afforded deliberate targeting of the importance of multi-disciplinary teamwork in patient safety. The simulation event was feasible at low monetary, time, and human resource costs. This approach offers a scalable instructional design that targets inter-professional learning.